A Needs Assessment of Guidance and Counselling Services in Vocational High Schools - Aulia Fitri; Chairunnisa Chairunnisa (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to analyse the implementation of student needs assessment as a foundation for the development of guidance and counselling services in vocational high schools. This research employed a descriptive qualitative method, with School Counsellors at Diponegoro Vocational High School in Depok as subjects, selected through purposive sampling. Data were collected through in-depth interviews, direct observations, and document analysis, based on the needs assessment theory of Gysbers and Henderson. Data analysis was conducted using the interactive model by Miles and Huberman, which comprises three stages: data reduction, data display, and conclusion drawing. The results indicate that a needs assessment at Diponegoro Vocational High School has been conducted; however, it has not yet reached an optimal level. The main limitations include insufficient time, an unbalanced counsellor-to-student ratio, the absence of official guidelines and systemic support that has not been met. As a result, the needs assessment tends to be reactive and does not fully address students' comprehensive needs, especially in the career domain. This condition leads to guidance and counselling programs that have not fully addressed students' actual needs in the personal, social, academic, and career domains. The findings of this study provide a basis for developing policies to improve School Counsellors' competence through standardised, contextually relevant training programs in needs assessment.